Cinematic countrysides - Fish, Robert (Inside popular film., 2018)
Recent years have witnessed an explosion of interest in the 'spatialities of cinema' across the social sciences and humanities, yet to date critical inquiry has tended to explore this issue as a question of the 'city' and the 'urban'. For the first time, leading scholars in geography, film and cultural studies have been drawn together to explore the multiple ways in ideas of cinema and countryside are co-produced: how 'film makes rural' and 'rural makes film'. From the expanse of the American great west to the mountainous landscapes of North Korea, Cinematic Countrysides draws on a range of popular and alternative film genres to demonstrate how film texts come to prefigure expectations of rural social space, and how these representations come to shape, and be shaped by, the material and embodied circumstances of 'lived' rural experience. At the heart of this volume's varied apprehensions of the 'cinematic countryside' is a concern to argue that ideas of rurality in film are central to wider questions of 'modernity' and 'tradition', 'self' and 'other', 'nationhood' and 'globalisation', and crucially, ones that are central to an account of the 'cinematic city'.